The Transformation of Qur'anic Literacy in the Digital Age: Reorienting Spiritual Values in Contemporary Islamic Education - Anton Sulistio; Nasril; Ridha Kurniawan; Hufri; Muhammad Ramadhan; Samsoo Sa-U (Journal Innovative Practices in Education (JIPE), 2025)
The digital era has transformed the practice of Qur'anic literacy, shifting it from traditional mediums to digital platforms. While enhancing accessibility and efficiency, this transformation potentially diminishes the spiritual values that are central to Islamic education. The knowledge gap lies in the absence of a conceptual framework that holistically integrates technological advantages with the preservation of spiritual values. This qualitative library research analyzed primary and secondary sources to address this gap. The findings reveal that: (1) digital platforms revolutionize learning methods but potentially weaken sacred and communal dimensions; (2) virtual communities emerge that adapt traditional values; (3) an integrative framework was identified where technology serves as a means (wasilah) rather than replacing the teacher's role. The research concludes that reorienting spiritual values is not about rejecting technology, but rather positioning it within Islamic ontological and axiological frameworks. Practically, these findings offer a blended learning model for basic Islamic education that combines digital applications with direct teacher guidance, while opening space for developing digital spirituality measurement tools in future research.